ANALISIS KONSEP DIRI RENDAH PADA PESERTA DIDIK SMP NEGERI 7 SUNGAI RAYA - Pariana Pariana; Luhur Wicaksono; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to obtain an overview of the characteristics of students who have a low self-concept, the factors that cause students who have low self-concept, the role of parents in increasing positive self-concept, the efforts that have been made by the Guidance and Counseling teacher to students who have self-concept. at SMPN 7 Sungai Raya. The research method used is descriptive with a survey research form. This research uses a qualitative approach. The subjects in this study were three students along with their close friends and counseling teachers. Data collection techniques used questionnaires and interviews. Based on the results of the research that has been done, the characteristics of children who have a low self-concept are irritable, difficult to accept input from others and difficult to interact. The factors that cause students to have a low self-concept are less relationship with classmates, less widespread friends, lack of communication with parents. The role of parents in increasing positive self-concept is caring for children, providing solutions when children share problems, inviting socializing. Efforts made by counseling teachers in dealing with low self-concept in students are individual counseling, group guidance, home visits.Keywords: Concept of inferiority